COORDINATED POLYMERS: SYNTHESIS, STRUCTURE PROPERTIES AND POTENTIAL APPLICATIONS (American Journal of Pedagogical and Educational Research, 2025)
This article covers the issues of synthesis of coordinated polymers, their structural properties and potential applications. During the study, types of structure of metal-ligand-based coordinated polymers, their physicochemical properties and functional capabilities were analyzed in depth. Solvothermal, gel reactions and modular approaches were used as synthesis methods. The resulting polymers were analyzed by X-ray diffraction, FTIR spectroscopy, thermal analysis, and BET surface measurements. The results of the structural analysis showed that the coordinated polymers exhibited microporous and nano-sized structure. The possibility of using polymers in gas storage, catalysis and drug transportation were also experimentally evaluated. The results of the study show that coordinated polymers are recognized as promising materials in modern materials science and industrial chemistry.